2020
DOI: 10.1051/bioconf/20201800021
|View full text |Cite
|
Sign up to set email alerts
|

Biological effectiveness of polyfunctional biopreparations in soft wheat cultivation and assessment of crop quality based on NDVI index

Abstract: The influence of Bacillus subtilis strains and chitosan complexes on the soft wheat productivity and its infection with disease agents was determined in order to develop new preparative forms of polyfunctional biopreparations. The prospects of using polyfunctional preparations, combined the beneficial properties of microorganism strains as pathogen antagonists and chitosan as plant disease resistance activator has been shown the study. Their effectiveness has been convincingly demonstrated in protecting wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The influence of Bacillus subtilis strains and chitosan complexes on the productivity of common wheat and their infection with pathogens was determined after the development of preparative forms of multifunctional biopreparations. Studies have shown the effectiveness of polyfunctional preparations, together with strains of microorganisms as pathogen antagonists, and chitosan as an activator of plant disease resistance in protecting wheat from root rot, increasing yield and improving grain quality, best adapted to agri-ecological environmental factors [42]. In modern agricultural production, the application of innovative technologies has been evaluated as the physicochemical properties of nanoparticles contribute to biocompatibility and biological activity by interaction with wheat and other crops.…”
Section: Multicriteria Evaluation Of the Optimal Bio-impact Effective...mentioning
confidence: 99%
“…The influence of Bacillus subtilis strains and chitosan complexes on the productivity of common wheat and their infection with pathogens was determined after the development of preparative forms of multifunctional biopreparations. Studies have shown the effectiveness of polyfunctional preparations, together with strains of microorganisms as pathogen antagonists, and chitosan as an activator of plant disease resistance in protecting wheat from root rot, increasing yield and improving grain quality, best adapted to agri-ecological environmental factors [42]. In modern agricultural production, the application of innovative technologies has been evaluated as the physicochemical properties of nanoparticles contribute to biocompatibility and biological activity by interaction with wheat and other crops.…”
Section: Multicriteria Evaluation Of the Optimal Bio-impact Effective...mentioning
confidence: 99%
“…One of the main trends in modern crop production is the use of plant protection agents and technologies facilitating the effective control of harmful organisms and contributing to the reduction in chemicals. The optical characteristics of crop phytosanitary states can be determined by NIR-related VIs such as the NDVI (Normalized Difference Vegetation Index), which serves as a relative indicator of the amount of photosynthetically active biomass and can accurately determine changes in crop states [ 7 ]. The NDVI is probably the most utilized and well-known VI, and it consists of a linear algebraic relation between red and NIR radiation which is measured by costly and specialized multi-sensor cameras.…”
Section: Introductionmentioning
confidence: 99%